2007
DOI: 10.1111/j.1572-0241.2007.01224.x
|View full text |Cite
|
Sign up to set email alerts
|

Do Consensus Indications for Resection in Branch Duct Intraductal Papillary Mucinous Neoplasm Predict Malignancy? A Study of 147 Patients

Abstract: Suggested consensus indications for resection identify all patients with malignancy; however, their specificity is low. In the short term it would be safe to follow patients without these features.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
144
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 247 publications
(150 citation statements)
references
References 20 publications
4
144
0
2
Order By: Relevance
“…Since their publication in 2006, studies have shown the Sendai guidelines to be highly sensitive (approximately 97%), but very nonspecific (approximately 29%) for the detection of a malignant mucinous cyst. [8][9][10] Cyst size and nonspecific patient symptoms have proven to be poor predictors of malignancy. 11,12 Although the majority of patients with cancer were detected, many patients already had invasive cancers at the time of surgical resection.…”
Section: 6mentioning
confidence: 99%
“…Since their publication in 2006, studies have shown the Sendai guidelines to be highly sensitive (approximately 97%), but very nonspecific (approximately 29%) for the detection of a malignant mucinous cyst. [8][9][10] Cyst size and nonspecific patient symptoms have proven to be poor predictors of malignancy. 11,12 Although the majority of patients with cancer were detected, many patients already had invasive cancers at the time of surgical resection.…”
Section: 6mentioning
confidence: 99%
“…While these guidelines had a sensitivity of 100%, multiple studies indicated low specificity ranging from 23%-31%. 10,11 Subsequently, revised Fukuoka guidelines were presented in 2012 with stricter surgical criteria: pancreatic duct ≥ 10 mm, an enhancing solid component, or obstructive jaundice with a pancreatic head cyst. 8 While this resulted in improved specificity, there was a loss in sensitivity to detect advanced neoplasia and no statistical differences when compared to the Sendai guidelines.…”
Section: Guidelines For Screening Pancreatic Cystic Lesionsmentioning
confidence: 99%
“…Communicates with MPD and no MPD dilatation. 12-47 [16][17][18][19][20] Mixed Satisfy criteria for both main duct and branch duct IPMN. 38-65 9,[14][15][16] Mucinous cystic neoplasm Mucinous.…”
Section: -68mentioning
confidence: 99%